Performance measurement framework for private tahfiz schools in Malaysia: the regulators and operators perspective / Mohd Yassir Jaaffar … [et al.] - Jaaffar, Mohd Yassir; Bani, Hamidah; Muhammad, Anuar; Mohd Noor, Abd Halim (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This study is intended to gauge the elements of performance measurement framework for private tahfiz schools (PTS) in Malaysia and to determine the expectation gap between regulators and tahfiz operators on the performance measurement. Series of interviews were conducted with the representatives from the State Islamic Religious Council (SIRCs) and tahfiz school operators. Thematic analysis using Atlas.ti showed that there are four (4) main elements of PTS performance measurement namely school infrastructure, students’ achievement, students’ evaluation and clustering. These elements are essential principles to be used in evaluating PTS capability in providing tahfiz education. Future research could focus on quantifying the quality indicators of PTS performance measurement.